2011
DOI: 10.1002/pds.2104
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term use of zopiclone, zolpidem and zaleplon among Danish elderly and the association with sociodemographic factors and use of other drugs

Abstract: The results indicate that the guidance for length of use is not followed. Long-term use of zopiclone, zolpidem and zaleplon is associated with sociodemographic factors and use of other drugs, particularly from ATC group N.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 16 publications
5
36
2
1
Order By: Relevance
“…Older age was a strong predictor for long-term use of benzodiazepines, which is consistent with previous studies (Andersen and Frydenberg, 2011;Cunningham et al, 2010;Demyttenaere et al, 2008;Fang et al, 2009). It is possible that these findings are partly explained by other health problems or co-morbidities in older age.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Older age was a strong predictor for long-term use of benzodiazepines, which is consistent with previous studies (Andersen and Frydenberg, 2011;Cunningham et al, 2010;Demyttenaere et al, 2008;Fang et al, 2009). It is possible that these findings are partly explained by other health problems or co-morbidities in older age.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the primary health care centres were located in urban and rural areas as well as in both the Southern and Northern parts of Stockholm The following covariates were included in the model: age, gender, country of origin, income, education, social welfare and marital status. These covariates were included because previous research has shown that sociodemographic factors are related to psychiatric disorders (Andersen and Frydenberg, 2011;Bayard-Burfield et al, 2001;Demyttenaere et al, 2008;Fang et al, 2009;Hjern, 2001;Quigley et al, 2006;Sonnenberg et al, 2012). Age was divided into five categories: 25-44, 45-64, 65-74, and 85+ years.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations